172k views
2 votes
Solve. x+y+z=−4 2x+3y−2z=10 −x+2y−3z=−12 Enter your answer, in the form (x,y,z), in the boxes in simplest terms. ( , , )

User Hajikelist
by
4.8k points

1 Answer

4 votes

Answer:

(13, -10, -7)

Explanation:

Given

x+y+z=−4 .................. 1

2x+3y−2z=10 .................... 2

−x+2y−3z=−12 ................... 3

Reduce the equation to two equations, two unknowns:

Add eqn 1 and 3

y+2y+(z-3z) = -4-12

3y - 2z = -16 .......... 4

Also multiply eqn 3 by 2:

−2x+4y−6z=−24 ................... 5

Add 2 to 5:

3y+4y+ (-2z-6z) = 10-24

7y-8z = -14 ............... 6

Equate 4 and 6

3y - 2z = -16 .......... 4 * 4

7y-8z = -14 ............... 6 * 1

...............................................

12y - 8z = -64

7y-8z = -14

Subtract the resulting equations

12y-7y = -64+14

5y = -50

y = -50/5

y = -10

Substitute y = -10 into equation 4 to get z:

3y - 2z = -16

3(-10)-2z = -16

-30-2z = -16

-2z = -16+30

-2z = 14

z = 14/-2

z = -7

Substitute y = -10, z = -7 into eqn 1 to get x:

x+y+z = -4

x-10-7 = -4

x-17 = -4

x = -4+17

x = 13

Hence (x, y, z) is (13, -10, -7)

User Ember
by
5.1k points